The Need to Employ Knowledge Management to Boost the Quality of Services in Modern Organization, Especially Libraries - Faezeh Farhoodi; Fariborz Doroudi (Iranian Journal of Information Processing & Management, 2009)
The present paper deals with the role of played by knowledge management in organizations and its impact on their improved operations, including libraries. The KM mission within an organization is to transform the tacit knowledge of employees into an important source for decision making as well as proactive documentation of explicit knowledge for achieving organizational goals. The closer man’s abilities, understanding, cognition and information are matched, the more one could be optimistic about generation of a more effective and applied knowledge. Nowadays organizations should not solely consider their financial holdings as their assets, rather the collective knowledge of those employed within an organizations are one of its most important asset on which the management must duly invest.